A Counterexample to Variabilism. (29th February 2016) - Capraru, Mihnea D. I.
Abstract: Recent literature contains influential arguments for variabilism, the view that we should understand proper names as analogues not of constants but of variables. In particular, proper names are said to sometimes take semantic values that are not referential but purely general. I present a counter-example to this view.